A Cross-Sectional Study of Perceived Stress, Mindfulness, Emotional Self-Regulation, and Self-Care Habits in Registered Nurses at a Tertiary Care Medical Center - Elaina Vivian MPH, CPHQ; Hellen Oduor MBChB, MPH, CPHQ, LSSGB; Sharina R. Arceneaux DNP, RN-B; Jasmine A. Flores MSIHCM, BSN, RN; Allison Vo MPA/HCA, BSN, RN, OCN; Barbara Madson Madden MSN, RN (SAGE Publishing, 2019)
Introduction Workplace stress and burnout may influence nurses' physical and emotional well-being, which can impact the quality of care patients receive and their overall satisfaction with their hospitalization. Objectives The objectives of the study were to evaluate whether there are significant statistical relationships between nurses' perceived stress, frequency of stressors, mindfulness, emotional self-regulation, self-care habits, and patient satisfaction scores. Methods The study took place over the course of 4 weeks. In this study, 340 nurse participants were surveyed using cross-sectional voluntary sampling design. The survey included previously developed and validated instruments. SAS v. 9.4 was used for statistical analysis. Results Significant differences were noted in average patient satisfaction scores by perceived stress; major nursing units in the Death and Dying, Conflict with Physicians, Lack of Support, and Work Load subscales of the Nursing Stress Scale; and major nursing units and dispositional mindfulness. Conclusions Hospital administrators can use this information in their organizations and set priorities and tailor mindfulness-based stress-reduction interventions for nursing professionals.